Development and Reliability of the Ankle Instability Instrument - Docherty, Carrie L (National Athletic Trainers Association, 2006)
Context: Functional ankle instability has been defined in a variety of ways. Factors that are frequently used in this definition include a history of a severe ankle sprain, a history of multiple ankle sprains, and a recurrent feeling of instability or “giving way.” With all the variations in defining functional ankle instability, it becomes increasingly important to develop a more consistent framework for assessing this instability. Objective: To develop a new ankle instability assessment tool, the Ankle Instability Instrument, and evaluate the reliability of this instrument. Design: Test-retest reliability was evaluated using intraclass correlation coefficients (2,1) for each item, each factor, and the total score between test days 1 and 2. Cronbach alpha was calculated to estimate internal consistency of the 12 items. Setting: Classrooms, offices, athletic fields, and private residences. Patients or Other Participants: College students (29 males, 72 females, age = 20.7 ± 2.7 years), including 73 (72%) with and 28 (28%) without a history of ankle injury. Main Outcome Measure(s): Subjects were asked to complete the Ankle Instability Instrument on 2 occasions approximately 1 week apart. Results: An exploratory factor analysis of the Instrument produced 3 factors and reduced it from 21 to 12 items. The factors accounted for 32.3%, 10.7%, and 7.0% of the variance, respectively. Together, these factors accounted for 50.0% of the variance in the responses to the Instrument. Test-retest reliability ranged from .70 (SEM = 0.28) to .98 (SEM = 0.06) for the individual items and .95 (SEM = 1.85) for the Instrument overall. The Cronbach alpha coefficient was .92 for factor 1 (severity of initial ankle sprain), .87 for factor 2 (history of ankle instability), .81 for factor 3 (instability during activities of daily life), and .89 for the Instrument overall. Conclusions: The creation of the Ankle Instability Instrument is a first step in recognizing a more objective way of identifying patients suffering from functional ankle instability. The high reliability we found shows that self-reporting of ankle symptoms is a feasible, appropriate way to obtain information on the presence of instability symptoms. Additionally, through this preliminary study, we found 3 factors that represent unique and important components of functional ankle instability. Clinicians and researchers can, therefore, use these 12 items, either alone or in combination with other information, to determine if functional ankle instability is present.